PARAMETRIC STUDY OF STRUCTURAL PERFORMANCE OF SINGLE SYSTEM SPSW AND DUAL SYSTEM SMF-SPSW - Rifqi Pratama, Abrar
Steel plate shear walls (SPSW) and special moment frame (SMF) are structural systems that are known to have good seismic performance factors. Based on SNI 1726-2019 for a single system SPSW the parameters R = 7, ?0 =2 and Cd = 6 are given, while for the dual system SMF-SPSW the parameters R = 8, ?0 =2.5 and Cd = 6.5 are given. In this research, a parametric study was carried out to study the performance of structures designed in accordance with SNI 1726-2019, due to the addition of the SMF system to the SPSW system as a dual SMF-SPSW system. Nonlinear analysis uses Perform 3D v 8.0 software to study structural performance regarding drift, ductility, strength and dissipated energy parameters. This research uses 3 models of 10-story structures with a height of 45 meters located in Jakarta with seismic design category D, which have been designed in accordance with SNI 1726-2019. The variations of the model used are a single system SPSW, a dual system SPSW with 2 SMF spans (dual system SPSW 2 SMF) and a dual system with 3 SMF spans (dual system SPSW 3 SMF). Design of steel sectional elements refers to AISC 360-16 and AISC 341-16 as well as to ASCE/SEI 41-17 nonlinear properties. The performance of the structure was evaluated using pushover analysis, cyclic analysis, and nonlinear time history analysis (NLTHA). The research results show that the addition of SMF to a single system SPSW significantly increases the drift, ductility, strength and energy dissipation of the structure. Likewise, the addition of 2 SMF spans to 3 SMF spans increases drift, ductility, strength and energy dissipation. Apart from this, the addition of SMF to a single system SPSW also causes a gradual increase in the monotonic and hysteresis curves before reaching its peak strength. The decrease after peak strength also experienced differences, spesifically in the single system SPSW there was a significant decrease of more than 20% after failure of the SPSW strip element, while in the dual system SMF-SPSW the decrease occurred slowly. Then the effect of adding SMF to a single system SPSW also makes the hysteresis curve fatter, which means greater energy dissipation. Based on the NLTHA results, it can be seen that the type and duration of the earthquake affect the resulting dissipated energy results. For an earthquake with a reverse type and a duration of 70 seconds, it can be seen that the dual system SMF-SPSW dissipates more energy than the single system. Meanwhile, earthquakes with strike slip and reverse oblique types with durations of 45 seconds and 16 seconds appear to have almost the same energy dissipation for the single system SPSW and the dual system SMF-SPSW.